The Existence of Badung Market as a Public Space in Community Order in the City of Denpasar - Gede Ari Putra, Dewa; Widiastuti, Widiastuti; Ketut Agusintadewi, Ni (Universitas Ibn Khaldun Bogor, 2023)
The existence of traditional markets and modern markets, especially in Denpasar City, has become an inseparable part of urban life. Some opinions reveal that with the development of modern markets, traditional markets have become increasingly marginalized. Badung Market is a traditional market located in the center of Denpasar City, Jalan Gajah Mada. The existence of Badung Market as a public space is also known as an icon or identity for the City of Denpasar. Maintaining the social life in Badung Market which is created by the existence of traditions in business life in the Badung Market environment which is the basis for traders to act in selling daily at Badung Market. The purpose of this study is to determine the existence of the Badung Market in Denpasar City. This study uses a mix method that combines quantitative methods with qualitative methods using qualitative methods which are more dominant than quantitative methods. Through qualitative data collection it is processed into quantitative, from quantitative analysis then the findings are explained or interpreted. The research approach used is a case study or case study, this case study approach is used to understand the conditions of the existence of the Badung Market in a social setting in Denpasar City. The efforts of traders to maintain social capital consisting of norms, trust, and bargaining can strengthen loyal networks of market visitors to keep shopping in traditional markets so as to maintain the existence of traders and the existence of traditional markets. From the many determinants of the existence of traditional markets, it can be concluded that the key indicator determining the existence of traditional markets lies in social capital because of its large role.